2015
DOI: 10.1007/s00520-015-2614-z
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine use in patients with hematological cancers in Malaysia

Abstract: In view of the high prevalence of CAM use in patients with hematological cancers, it is important that the physicians play an active role in seeking information from patients and to monitor possible drug-vitamin-herbal interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
5
16
0
Order By: Relevance
“…in Palestine 69.5%, Malaysia 70.2%, and Ethiopia 79% . 15,16 In this survey, women accounted for 62% of patients, similar to research by Ustundang. 17 The internet was the main source of knowledge about herbal preparations for 19.6% of the respondents, while the recommendation of doctor and pharmacist accounted for 14.1%.…”
Section: Discussionsupporting
confidence: 81%
“…in Palestine 69.5%, Malaysia 70.2%, and Ethiopia 79% . 15,16 In this survey, women accounted for 62% of patients, similar to research by Ustundang. 17 The internet was the main source of knowledge about herbal preparations for 19.6% of the respondents, while the recommendation of doctor and pharmacist accounted for 14.1%.…”
Section: Discussionsupporting
confidence: 81%
“…More than two-thirds of the participants who reported using dietary supplement in the present study, had two or more comorbidities. Supplement use was also highest among elderly individuals diagnosed with oncologic disorders, as previously reported [6466] though scientific evidence on the safety and efficacy of supplements in cancer has so far been inconclusive (reviewed in [67]). In the present study, a significant association between supplement use and potential drug-drug interactions was found and this remained significant after adjusting for age, gender, ethnicity and multiple comorbidities.…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, a significant association between supplement use and potential drug-drug interactions was found and this remained significant after adjusting for age, gender, ethnicity and multiple comorbidities. Thus, the high use of supplements among elderly people is a major concern, particularly given that a majority of patients in our setting have previously reported not to disclose information on their supplement intake to their healthcare practitioners [64, 65]. …”
Section: Discussionmentioning
confidence: 99%
“…After controlling for covariates, we found that CAM use uniquely explained 8.7% and 8.8% of variances in anxiety and depression, respectively, suggesting the potential efficacy of CAM use on emotional status. Some previous studies reported nonsignificant associations between CAM use and anxiety and depression, 28,44 whereas in other studies, CAM treatment was reported to improve anxiety and depression. 50,51 Given the competing views among previous reports, 10,23 the correlation between CAM use and emotional well-being remains unclear.…”
Section: Discussionmentioning
confidence: 85%
“…CAM use has been higher in female gender, 25,41 younger age, 41,42 higher education level, 18,41–43 higher income, 25,41 palliative care setting, 32 and positive family history of advanced cancer (stage IV and distant metastasis), 18,42,43 although there was a nonsignificant association between CAM use and income. 44 In addition, more information on CAM appears to promote more CAM use. 45 Patients in this study indicated that only 36% consulted with their physicians.…”
Section: Discussionmentioning
confidence: 99%